Greater efficiency in criminal investigations provided for in the anti-crime law and its constitutionality (Revista do Tribunal Regional Federal da 3ª Região, 2020)
Law nº 13.964, of december 24, 2019 (anti-crime law), causes significant changes in criminal procedural law and Brazilian criminal law. The present study verifies whether the monitoring of audio and video in maximum security criminal establishments improves criminal investigation. A controversial issue is whether state enforcement offends prisoners “right to privacy and violates lawyers” functional prerogatives. Finally, it remains to be seen whether such legislative changes are compatible with the Federal Constitution and human rights. At the end of the work, it is understood that procedural and criminal changes strengthen the mechanisms of criminal investigation in the fight against crime, being in line with the Constitution and international standards.
Keywords: article 11 of Law No. 13.964/2019; monitoring of prison by audio and video; investigative efficiency; constitutuionality